2010
DOI: 10.1080/14616691003596973
|View full text |Cite
|
Sign up to set email alerts
|

Mother's Employment: Cultural Imprint or Institutional Governance?

Abstract: In the public and scientific discussion on the political scope of action for improving employment opportunities for mothers, cultural aspects of female labour market participation often remain ignored. This study argues that employment decisions of mothers vary not only with the institutional settings but also with the dominant representative culture of a region. In order to study the effects of culture and institutions on maternal employment, Belgium, East, and West Germany are selected for empirical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…For a number of European countries, they find public childcare facilities increase female labor force participation. These findings are confirmed by Gornick et al (1997) as well as Hummelsheim and Hirschle (2010). We expect that higher enrollment in childcare is associated with higher FLPRs of women of 25 and above (H7a).…”
Section: (C) Familiessupporting
confidence: 83%
See 1 more Smart Citation
“…For a number of European countries, they find public childcare facilities increase female labor force participation. These findings are confirmed by Gornick et al (1997) as well as Hummelsheim and Hirschle (2010). We expect that higher enrollment in childcare is associated with higher FLPRs of women of 25 and above (H7a).…”
Section: (C) Familiessupporting
confidence: 83%
“…Clark, Ramsbey, & Stier Adler, 1991;Haghighat, 2002;Hummelsheim & Hirschle, 2010;Lincove, 2008). Contrary to studies into the effect of the intensity of religious views or practices (c.f.…”
Section: (D) Gender Ideologiesmentioning
confidence: 83%
“…This argument is supported by the findings of different empirical studies (Hummelsheim and Hirschle, 2010;Mandel, 2009;Saxonberg and Szelewa, 2007).…”
Section: The Impact Of Family Policiesmentioning
confidence: 70%
“…Family policy measures, therefore, might be used in quite different ways by mothers in either part of the country, or might have different consequences in East and West. This is illustrated by a recent comparison of Belgium, West Germany, and East Germany (Hummelsheim and Hirschle, 2010). Whereas East Germany is characterized by an egalitarian gender culture, Belgium and, to a somewhat lesser degree, West Germany continue to be dominated by traditional family values, which impact mothers' work behaviour beyond existing institutional opportunities.…”
Section: Mothers' Labour Market Participationmentioning
confidence: 99%
“…Whereas East Germany is characterized by an egalitarian gender culture, Belgium and, to a somewhat lesser degree, West Germany continue to be dominated by traditional family values, which impact mothers' work behaviour beyond existing institutional opportunities. Using Belgium as an example, the authors conclude that providing IJSSP 32,9/10 extensive publicly subsidized child care will not automatically increase mothers' employment rates unless the notion of working mothers is culturally approved (Hummelsheim and Hirschle, 2010). Gupta et al (2008) have found similar differences between the "Nordic countries", which are often lumped together in their role as egalitarian welfare state leaders.…”
Section: Mothers' Labour Market Participationmentioning
confidence: 99%